SKRINING FITOKIMIA DAUN TEH HIJAU (CAMELLIA SINENSIS L.) DAN BIJI LADA HITAM (PIPER NIGRUM L.) - Sandhori, Fajar Jamaluddin; Hanif Rifqi Prasetyawan; Farida Istiqamah; Ilham Robbynoor Sulistiyono; Rizkiyatul Hasanah (Jurnal Medicare, 2025)
Plants are the main source of secondary metabolites that have important biological potential. This study aims to screen the phytochemicals of green tea leaves and black pepper to identify the classes of active compounds contained within them. Extraction was performed using the maceration method with 96% ethanol over three days, followed by qualitative phytochemical testing (alkaloids, flavonoids, saponins, tannins, triterpenoids, steroids, polyphenols, and anthraquinones). Green tea leaves contain alkaloids, triterpenoids, flavonoids, polyphenols, and anthraquinones. Black pepper contains alkaloids, saponins, triterpenoids, steroids, and flavonoids, but does not contain polyphenols, tannins, or anthraquinones. The differences in the composition of active compounds indicate distinct therapeutic potentials in the two plants and support their use as natural medicinal ingredients.